Lightweight thermal insulation building block based on construction waste and preparation method thereof
Patent Information
- Application Number
- CN202610910071.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-23
- Publication Date
- 2026-10-23
AI Technical Summary
这种薄弱的界面结合状态,不仅进一步削弱了砌块的力学性能,还会导致外界的水、酸碱介质、二氧化碳等易通过界面缝隙渗透至砌块内部,引发砌块耐酸碱腐蚀、抗冻融循环、抗碳化能力显著下降,长期使用过程中易出现表面起砂、开裂、剥落等损坏现象,无法满足建筑墙体长期服役的耐久性要求,也不符合绿色建材的长效使用标准
1、本发明采用巴氏芽孢杆菌裂解制备的脲酶高效催化尿素水解,持续、均匀生成碳酸根离子,耐高碱产碳酸酐酶菌粉可进一步催化体系中二氧化碳水合,辅助补充碳酸根并精细调控碳酸钙结晶速率与晶型,使生成的碳酸钙以纳米晶体形式,优先在再生骨料内部孔隙、微裂纹处原位沉积、生长,逐步填充贯通孔洞与结构缺陷,实现裂纹桥接、孔隙封堵,显著提高再生骨料密实度与本体力学强度,从根源解决建筑垃圾骨料疏松、强度低的缺陷,从而显著提高砌块的力学性能。
Smart Images

Figure CN122958141A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of thermal insulation block technology, specifically to a lightweight thermal insulation block based on construction waste and its preparation method. Background Technology
[0002] With the rapid advancement of urbanization in my country, the pace of urban construction and renovation is accelerating, leading to an explosive growth in the amount of construction waste. However, the resource utilization rate of this waste is insufficient, with the vast majority being disposed of through open dumping or landfill. This not only occupies significant land resources but also pollutes groundwater through leachate and the atmosphere through dust, creating a severe ecological burden. Simultaneously, the demand for sand and gravel aggregates in the construction industry continues to rise, while natural sand and gravel resources are becoming increasingly depleted. Over-exploitation has resulted in riverbed decline and mountain damage, further exacerbating ecological and environmental pressures. Against this backdrop, processing construction waste into recycled aggregates to replace natural aggregates in the production of building blocks has become an important pathway to achieve resource utilization of construction waste, alleviate resource shortages, and promote the green and low-carbon development of the construction industry.
[0003] Currently, the technology for preparing masonry blocks using recycled aggregates from construction waste still faces many bottlenecks that urgently need to be addressed, severely restricting its large-scale and high-quality application: First, recycled aggregates from construction waste have inherent performance defects, making it difficult for the mechanical properties of the blocks to meet engineering requirements. Recycled aggregates from construction waste mainly originate from the crushed and processed products of waste concrete, waste bricks, and waste mortar. Their surfaces are rough, angular, and often contain incompletely detached hardened cement mortar, resulting in a loose internal structure, high porosity, high crushing index, low apparent density, and significantly lower mechanical strength than natural aggregates. This inherent defect directly leads to insufficient density in the prepared recycled aggregate blocks, resulting in poor core mechanical properties such as compressive and flexural strength. This makes it difficult to meet the basic structural strength requirements of building walls, thus limiting their application.
[0004] Secondly, the weak interfacial bonding between recycled aggregates and the cementitious matrix leads to insufficient durability and a significantly shortened service life of the blocks. During the block preparation process, the porous structure and residual mortar layer on the surface of the recycled aggregates create a weak interfacial transition zone between them and the cementitious matrix such as cement and fly ash. This zone is prone to micropores and microcracks, resulting in extremely low interfacial bond strength. This weak interfacial bonding not only further weakens the mechanical properties of the blocks but also allows external substances such as water, acids, alkalis, and carbon dioxide to easily penetrate into the block through the interfacial gaps. This significantly reduces the blocks' resistance to acid and alkali corrosion, freeze-thaw cycles, and carbonation. Over long-term use, the blocks are prone to surface sanding, cracking, and peeling, failing to meet the durability requirements for long-term service of building walls and the long-term use standards for green building materials.
[0005] Finally, traditional recycled building blocks generally suffer from poor thermal insulation and energy-saving performance, heavy weight, and insufficient crack resistance and impact resistance. Traditional recycled blocks are mostly prepared by mixing single recycled aggregates with cementitious materials, without specific optimization for thermal insulation and energy-saving performance. Their thermal conductivity is relatively high, resulting in poor thermal insulation and making it difficult to meet current building energy efficiency standards.
[0006] Therefore, developing a lightweight insulating block based on construction waste and its preparation method that can effectively solve the performance defects of recycled aggregates, weak interfacial bonding, and synergistic improvement of thermal insulation, mechanical properties, and durability, and realize the high-value-added resource utilization of construction waste, and meet the dual needs of building energy conservation and structural safety, has important practical significance and broad application prospects. Summary of the Invention
[0007] To address the shortcomings of existing technologies, the present invention aims to provide a lightweight thermal insulation block based on construction waste and its preparation method.
[0008] This invention provides a lightweight thermal insulation block based on construction waste, comprising: 60-70 parts by weight of modified recycled construction waste aggregate, 5-8 parts by weight of quartz sand, 8-15 parts by weight of hydrated sodium silicate, 20-30 parts by weight of fly ash, 8-12 parts by weight of composite cementitious agent, 2-3 parts by weight of modified starch, 12-15 parts by weight of deionized water and 0.5-1 parts by weight of thermal insulation aerogel. Modified construction waste recycled aggregate is obtained by first removing impurities from construction waste, crushing and screening, washing, then performing compound mineralization treatment with urease and high-alkali resistant carbonic anhydrase bacteria, spraying and coating with silicon-based composite functional liquid, and drying.
[0009] A method for preparing a lightweight thermal insulation block based on construction waste, characterized in that it comprises: S1: Preparation of silicon-based composite functional liquid; Mix 15-20 parts by weight of N-aminoethyl-3-aminopropyltrimethoxysilane, 40-50 parts by weight of ethanol, 15-20 parts by weight of γ-glycidyl etheroxypropyltrimethoxysilane, and 50-60 parts by weight of deionized water, stir, let stand to defoam, add sodium chloride and stir, adjust the pH to neutral, add boric acid, stir the reaction at a constant temperature, and cool to obtain a silicon-based composite functional liquid. S2: Preparation of modified recycled aggregate from construction waste; After construction waste is cleaned, crushed, screened, and washed, it undergoes mineralization treatment, and is finally sprayed with a silicon-based composite functional liquid and dried to obtain modified construction waste recycled aggregate. S3: Preparation of thermal insulation aerogel; Yttrium nitrate hexahydrate, tetraethyl orthosilicate, deionized water, and phosphoric acid were mixed in a specific ratio and magnetically stirred for a long time. Then, a polyvinyl alcohol solution was added and stirred to prepare a spinning precursor solution. The fiber membrane was obtained by electrospinning under high pressure, electrode spacing, and push speed. The fiber membrane was dried and calcined in stages to obtain yttrium-doped silica nanofibers. The fibers were ground and chopped, and then mixed with tetraethyl orthosilicate and acetic acid aqueous solution to prepare an impregnation solution. The fiber membrane was impregnated, stacked, frozen, and vacuum dried. Finally, it was calcined in stages at high temperature to obtain a thermal insulation aerogel. S4: Preparation of lightweight thermal insulation blocks; Modified recycled aggregate from construction waste, quartz sand, hydrated sodium silicate, and fly ash are mixed together, and then composite binder, modified starch, and deionized water are added and stirred to obtain a mixture. Then, thermal insulation aerogel is laid in the block mixture, and after vibration and pressure molding, static setting, and curing, lightweight thermal insulation blocks are obtained.
[0010] Preferably, S1: The preparation of the silicon-based composite functional liquid specifically includes the following steps: S1.1: Take 15-20 parts by weight of N-aminoethyl-3-aminopropyltrimethoxysilane, 40-50 parts by weight of ethanol, 15-20 parts by weight of γ-glycidoxypropyltrimethoxysilane, and 50-60 parts by weight of deionized water, mix them, stir at 300-500 rpm, and let stand to defoam for 10-12 hours to obtain a mixed solution; S1.2: Add 1.5-2 parts by weight of sodium chloride to the mixed solution, then stir and mix at 500-600 rpm for 20-30 min. Adjust the pH to neutral with 10 mol / L HCl solution, then add 6-8 parts by weight of boric acid. Place the mixture in a heat-collecting constant temperature magnetic stirrer and react at 55-58℃ and a stirring speed of 300-500 rpm for 2-3 h. Cool to room temperature to obtain the silicon-based composite functional liquid.
[0011] Preferably, S2: the preparation of modified recycled aggregate from construction waste specifically includes the following steps: S2.1: Remove impurities from construction waste, and crush the resulting waste concrete. Then, screen it through 5mm and 10mm square hole screens to obtain waste concrete with a continuous particle size of 5-10mm. Put the waste concrete into a rotary hot air vortex cleaner and process it for 25-40 minutes. After that, screen out the stripped dust and broken mortar through a vibrating screen to obtain clean construction waste recycled aggregate. S2.2: 10 9Cell / mL Bacillus pasteurellium lysate was lysed using an ultrasonic lysis method. After lysis, centrifugation and filtration were performed sequentially to obtain a urease solution. 10-12 parts by weight of 0.5-1 mol / L urea solution and 10-12 parts by weight of 0.5-1 mol / L calcium chloride solution were mixed, and then 4-5 parts by weight of urease solution were added. The mixture was stirred at 300-500 rpm for 1-2 min. After that, carbonic anhydrase-producing bacterial powder tolerant to high alkali was added, and the mixture was stirred again for 3-5 min to obtain a mineralized solution. S2.3: The surface-cleaned recycled aggregate from construction waste is pre-wetted with deionized water for 10-15 minutes, and then added to the mineralization solution to completely immerse the surface-cleaned recycled aggregate in the mineralization solution for 48-72 hours. After that, it is dried in an environment of 45-50℃ until the moisture content reaches 8-10% to obtain mineralized recycled aggregate. S2.4: The mineralized recycled aggregate is fed into a high-speed vortex spray coating machine, and a silicon-based composite functional liquid is sprayed through the spraying device. The spraying amount is controlled to be 2-3% of the aggregate mass. After the spraying is completed, the vortex state is maintained for 5-10 minutes. Then, hot air drying is carried out until the moisture content is ≤5% to obtain modified construction waste recycled aggregate.
[0012] Preferably, in step S2.1, the temperature of the rotary hot air vortex cleaner is 80-100℃ and the humidity is 10-30%RH.
[0013] Preferably, in step S2.3, the amount of carbonic anhydrase-producing bacterial powder added is 5-8 g / L based on the total volume of the mineralization solution, and the viable count of the carbonic anhydrase-producing bacterial powder is 1×10⁻⁶. 9 CFU / g.
[0014] Preferably, S3: the preparation of the thermal insulation aerogel specifically includes the following steps: S3.1: Mix yttrium nitrate hexahydrate, tetraethyl orthosilicate, deionized water and phosphoric acid in a mass ratio of 0.3:1:1:0.01. After mixing, stir the mixture in a magnetic stirrer at 300-500 rpm for 8-10 h to obtain a mixed solution. Add 10-12 parts by weight of a 10 wt% polyvinyl alcohol aqueous solution to 10-12 parts by weight of the above mixed solution and stir at 500-600 rpm for 3-4 h to obtain the precursor spinning solution. S3.2: Inject the precursor spinning solution into the syringe for electrospinning. The needle tip is the positive electrode connected to a 17kV high-voltage power supply, and the aluminum foil receiving plate is the negative electrode grounded. The distance between the positive and negative electrodes is 20-22cm, and the feeding speed is 0.6-0.8mL / h to obtain the precursor fiber membrane. Dry the precursor fiber membrane in a forced-air drying oven at 50-60℃ for 30-40min. After drying, transfer the precursor fiber membrane to a muffle furnace and heat it to 250℃ at a rate of 2℃ / min. Hold it at this temperature for 1-2h, then heat it to 700-800℃ at a rate of 4-5℃ / min and calcine it for 2-3h. Finally, cool it to room temperature at a rate of 4℃ / min to obtain the yttrium-doped silicon oxide nanofiber membrane. S3.3: Grind the above-mentioned yttrium-doped silica nanofiber membrane into short chopped fibers. Mix 60-70 parts by weight of deionized water, 0.3-0.4 parts by weight of tetraethyl orthosilicate and 0.02-0.03 parts by weight of acetic acid, and stir at room temperature for 6-8 hours. Then add 0.18-0.2 parts by weight of the ground short chopped fibers and stir at 1300-1500 r / min for 15-20 minutes to obtain the impregnation solution. S3.4: The unground yttrium-doped silica nanofiber membrane was completely immersed in the impregnation solution for 6-8 hours. After impregnation, the yttrium-doped silica nanofiber membrane was stacked layer by layer in a copper mold and laterally frozen at -110°C for 10-12 minutes. Then, it was vacuum freeze-dried. After the vacuum freeze-dried aerogel preform was demolded, it was placed in an alumina crucible. The alumina crucible was then placed in an air resistance furnace and heated from room temperature to 200-230°C at a rate of 2-3°C / min. After holding at this temperature for 1-2 hours, the temperature was increased to 700-800°C at a rate of 2-3°C / min and held for another 1-2 hours. Finally, the temperature was lowered to room temperature at a rate of 2°C / min to obtain a thermal insulation aerogel.
[0015] Preferably, S4: the preparation of lightweight thermal insulation blocks specifically includes the following steps: S4.1: Put 60-70 parts by weight of modified construction waste recycled aggregate, 5-8 parts by weight of quartz sand, 8-15 parts by weight of hydrated sodium silicate and 20-30 parts by weight of fly ash into a high-speed mixer and stir at 400-500 rpm for 5-8 minutes. Then add 8-12 parts by weight of composite cementitious agent, 2-3 parts by weight of modified starch and 12-15 parts by weight of deionized water, and continue to stir at 200-300 rpm for 30-40 minutes to obtain the block mixture. S4.2: Spread half of the above-mentioned block mixture into the bottom of the block mold and pre-press it flat. Then spread 0.5-1 parts by weight of thermal insulation aerogel, cover it with the remaining block mixture and scrape it flat. Press the block mixture into block blanks using a vibration pressing molding machine. Let the demolded block blanks stand for 1-2 days, then transfer them to a constant temperature and humidity curing chamber. Set the curing temperature to 30-35℃ and the humidity to 75%RH, and cure for 24-36 hours. Then place them in a natural environment for standard curing for 14 days. After curing, lightweight thermal insulation blocks are obtained.
[0016] Preferably, the composite gelling agent in step S4.1 is a mixture of gypsum powder and metakaolin in a weight ratio of 3:1.
[0017] Preferably, the modified starch in step S4.1 is hydroxypropyl starch.
[0018] The present invention has the following advantages: 1. This invention utilizes urease, prepared by the lysis of Bacillus pasteurellii, to efficiently catalyze the hydrolysis of urea, continuously and uniformly generating carbonate ions. The carbonic anhydrase-producing bacterial powder, resistant to high alkali, can further catalyze the hydration of carbon dioxide in the system, assisting in the replenishment of carbonate ions and finely controlling the crystallization rate and crystal form of calcium carbonate. This allows the generated calcium carbonate to preferentially deposit and grow in situ in the pores and microcracks within the recycled aggregate in the form of nanocrystals, gradually filling through-holes and structural defects, achieving crack bridging and pore sealing, significantly improving the density and bulk mechanical strength of the recycled aggregate, and fundamentally solving the defects of loose and low-strength construction waste aggregate, thereby significantly improving the mechanical properties of the blocks.
[0019] 2. In this invention, a silicon-based composite functional liquid is used to coat the surface of recycled construction waste aggregate. The silicon-based composite functional liquid is a compound of N-aminoethyl-3-aminopropyltrimethoxysilane and γ-glycidyl etheroxypropyltrimethoxysilane. Sodium chloride is used to adjust the ionic strength of the system, and hydrochloric acid is used to control the neutrality of the reaction environment to construct a dense inorganic-organic hybrid network. The silicon-based composite functional liquid is applied to the surface of the mineralized recycled aggregate by spray coating. On the one hand, the siloxane groups and the silanol groups on the aggregate surface undergo dehydration condensation to form Si-O-Si covalent bonds. On the other hand, the amino and epoxy groups undergo chemical bonding and hydrogen bonding with the cementing system. This process strengthens the aggregate-matrix interface bonding, eliminates weak transition zones at the interface, significantly improves interfacial bonding strength, and enhances the mechanical strength of the blocks. On the other hand, the aggregate is first mineralized to generate calcium carbonate crystals that fill the pores. On this basis, a silicon-based composite functional liquid is sprayed on. The organosilicon molecules can interact with the hydroxyl groups on the surface of the newly generated calcium carbonate, forming a dense coating film that can effectively seal the interconnecting pores and micro-cracks on the aggregate surface, further densifying the surface layer. At the same time, it blocks the intrusion of external moisture, acid and alkali media, and carbon dioxide, enhancing the alkali resistance of the coating film to resist the erosion of the cement-based system and improving the freeze-thaw resistance and acid and alkali resistance of the blocks.
[0020] 3. The thermal insulation aerogel incorporated in this invention introduces yttrium hexahydrate as a dopant source. After calcination, yttrium hexahydrate is transformed into yttrium oxide, which is doped into the silicon oxide nanofiber framework. Yttrium acts as a high-temperature stabilizer, inhibiting the crystal transformation and volume shrinkage of silicon oxide during calcination at 700℃, making the aerogel framework less prone to collapse at high temperatures. Furthermore, yttrium oxide has a high refractive index and a special lattice vibration absorption peak, which can effectively absorb and scatter infrared thermal radiation, significantly reducing the radiative thermal conductivity of the aerogel in high-temperature environments. This results in a slower temperature rise on the inner side of the insulation layer in scenarios such as high-temperature exposure in summer or fire hazards. In addition, the process combines lateral freezing and vacuum freeze-drying. Lateral freezing promotes unidirectional growth of ice crystals, which form a directionally arranged layered pore structure after drying. This structure forces hot air molecules attempting to flow to constantly impact the pore walls, and the mean free path of the airflow is strictly confined within the nanoscale pores, which significantly reduces the thermal conductivity of the aerogel. This effectively reduces the overall thermal conductivity of the block, improves its thermal insulation performance, and embeds the aerogel into the block in sheet form, avoiding the damage to the nanopore structure caused by mechanical stirring. This allows the block to maintain its lightweight properties while possessing excellent thermal insulation capabilities. Attached Figure Description
[0021] Figure 1 This is a process flow diagram of the preparation method of lightweight thermal insulation blocks based on construction waste used in an embodiment of the present invention. Detailed Implementation
[0022] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions of this invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of this invention.
[0023] The carbonic anhydrase-producing bacterium has the accession number CGMCC No. 29094 and is deposited at the China General Microbiological Culture Collection Center. This carbonic anhydrase-producing bacterium is existing technology, and this application does not intend to deposit it.
[0024] Example 1: A method for preparing lightweight thermal insulation blocks based on construction waste, referring to... Figure 1 ,include: S1: Preparation of Silicon-based Composite Functional Liquid S1.1: Take 15 parts by weight of N-aminoethyl-3-aminopropyltrimethoxysilane, 40 parts by weight of ethanol, 15 parts by weight of γ-glycidyl etheroxypropyltrimethoxysilane, and 50 parts by weight of deionized water, mix them, stir at 300 rpm, and let stand to defoam for 10 h to obtain a mixed solution. S1.2: Add 1.5 parts by weight of sodium chloride to the mixed solution, then stir and mix at 500 rpm for 20 min. Then adjust the pH to neutral with 10 mol / L HCl solution, then add 6 parts by weight of boric acid, and then place it in a heat-collecting constant temperature magnetic stirrer. Stir and react for 2 h at 55℃ and 300 rpm. Cool to room temperature to obtain silicon-based composite functional liquid. S2: Preparation of Modified Recycled Aggregate from Construction Waste S2.1: Remove impurities from construction waste, and crush the resulting waste concrete. Screen it through 5mm and 10mm square hole screens to obtain waste concrete with a continuous particle size of 5-10mm. Put the waste concrete into a rotary hot air vortex cleaner, set the temperature to 80℃ and the humidity to 10%RH, and process it for 25 minutes. Then, screen out the stripped dust and broken mortar through a vibrating screen to obtain clean construction waste recycled aggregate. S2.2: 10 9 Cell / mL Bacillus pasteurellium lysate was lysed using an ultrasonic lysis method. After lysis, centrifugation and filtration were performed sequentially to obtain a urease solution. Ten parts by weight of 0.5 mol / L urea solution and ten parts by weight of 0.5 mol / L calcium chloride solution were mixed, and then four parts by weight of urease solution were added. The mixture was stirred at 300 rpm for 1 min. Then, 5 g / L of carbonic anhydrase-producing bacterial powder was added and stirred again for 3 min to obtain a mineralized solution. S2.3: The surface-cleaned recycled aggregate from construction waste is pre-wetted with deionized water for 10 minutes, and then added to the mineralization solution to completely immerse the surface-cleaned recycled aggregate in the mineralization solution for 48 hours. After that, it is dried at 45°C until the moisture content reaches 8% to obtain mineralized recycled aggregate. S2.4: The mineralized recycled aggregate is fed into a high-speed vortex spray coating machine, and a silicon-based composite functional liquid is sprayed through a dual-fluid atomizing spray gun. The spraying amount is controlled to be 2% of the aggregate mass. After the spraying is completed, the vortex state is maintained for 5 minutes. Then, hot air drying is carried out until the moisture content is ≤5% to obtain modified construction waste recycled aggregate. S3: Preparation of thermal insulation aerogel S3.1: Yttrium nitrate hexahydrate, tetraethyl orthosilicate, deionized water and phosphoric acid are mixed in a mass ratio of 0.3:1:1:0.01. After mixing, the mixture is stirred at 300 rpm for 8 hours on a magnetic stirrer to obtain a mixed solution. 10 parts by weight of a 10 wt% polyvinyl alcohol aqueous solution are added to 10 parts by weight of the above mixed solution and stirred at 500 rpm for 3 hours to obtain the precursor spinning solution. S3.2: The precursor spinning solution is injected into the needle tube for electrospinning. The needle tip is the positive electrode connected to a 17kV high-voltage power supply, and the aluminum foil receiving plate is the negative electrode grounded. The distance between the positive and negative electrodes is 20cm, and the feeding speed is 0.6mL / h to obtain the precursor fiber membrane. The precursor fiber membrane is dried in a forced-air drying oven at 50℃ for 30min. After drying, the precursor fiber membrane is transferred to a muffle furnace and heated to 250℃ at a rate of 2℃ / min, held for 1h, then heated to 700℃ at a rate of 4℃ / min, calcined for 2h, and finally cooled to room temperature at a rate of 4℃ / min to obtain the yttrium-doped silicon oxide nanofiber membrane. S3.3: Grind the above-mentioned yttrium-doped silica nanofiber membrane into short chopped fibers, mix 60 parts by weight of deionized water, 0.3 parts by weight of tetraethyl orthosilicate and 0.02 parts by weight of acetic acid, and stir at room temperature for 6 hours. Then add 0.18 parts by weight of the ground short chopped fibers and stir at 130 r / min for 15 minutes to obtain the impregnation solution. S3.4: The unground yttrium-doped silica nanofiber membrane was completely immersed in the impregnation solution for 6 hours. After impregnation, the yttrium-doped silica nanofiber membrane was stacked layer by layer in a copper mold. Then, it was laterally frozen at -110°C for 10 minutes. After that, it was vacuum freeze-dried. After the vacuum freeze-dried aerogel preform was demolded, it was placed in an alumina crucible. Then, the alumina crucible was placed in an air resistance furnace and heated from room temperature to 200°C at a rate of 2°C / min. After holding at this temperature for 1 hour, the temperature was increased to 700°C at a rate of 2°C / min and held for 1-2 hours. Finally, the temperature was lowered to room temperature at a rate of 2°C / min to obtain a thermal insulation aerogel. S4: Preparation of lightweight thermal insulation blocks S4.1: Put 60 parts by weight of modified construction waste recycled aggregate, 5 parts by weight of quartz sand, 8 parts by weight of hydrated sodium silicate and 20 parts by weight of fly ash into a high-speed mixer and stir at 400 rpm for 5 min. Then add 8 parts by weight of composite cementitious agent, 2 parts by weight of hydroxypropyl starch and 12 parts by weight of deionized water and continue to stir at 200 rpm for 30 min to obtain block mixture. The composite cementitious agent is made by mixing gypsum powder and metakaolin in a weight ratio of 3:1. S4.2: Spread half of the block mixture into the bottom of the block mold and pre-press it flat. Then spread 0.5 parts by weight of thermal insulation aerogel, and then cover it with the remaining block mixture and scrape it flat. Press the block mixture into a block blank using a vibration pressing molding machine. Let the demolded block blank stand for 1 day, and then transfer it to a constant temperature and humidity curing chamber. Set the curing temperature to 30℃ and the humidity to 75%RH and cure for 24 hours. Then place it in a natural environment for standard curing for 14 days. After curing, lightweight thermal insulation blocks are obtained.
[0025] Example 2, a method for preparing lightweight thermal insulation blocks based on construction waste, see [link to example]. Figure 1 ,include: S1: Preparation of Silicon-based Composite Functional Liquid S1.1: Take 20 parts by weight of N-aminoethyl-3-aminopropyltrimethoxysilane, 50 parts by weight of ethanol, 20 parts by weight of γ-glycidoxypropyltrimethoxysilane, and 60 parts by weight of deionized water, mix them, stir at 500 rpm, and let stand to defoam for 12 hours to obtain a mixed solution. S1.2: Add 2 parts by weight of sodium chloride to the mixed solution, then stir and mix at 600 rpm for 30 min. Then adjust the pH to neutral with 10 mol / L HCl solution, then add 8 parts by weight of boric acid, and then place it in a heat-collecting constant temperature magnetic stirrer and react at 58℃ and a stirring rate of 500 rpm for 3 h. Cool to room temperature to obtain silicon-based composite functional liquid. S2: Preparation of Modified Recycled Aggregate from Construction Waste S2.1: Remove impurities from construction waste, and crush the resulting waste concrete. Then, screen it through 5mm and 10mm square hole screens to obtain waste concrete with a continuous particle size of 5-10mm. Put the waste concrete into a rotary hot air vortex cleaner, set the temperature to 100℃ and the humidity to 30%RH, and process it for 40 minutes. After that, screen out the stripped dust and broken mortar through a vibrating screener to obtain clean construction waste recycled aggregate. S2.2: 10 9 Cell / mL Bacillus pasteurellium lysate was lysed using an ultrasonic lysis method. After lysis, centrifugation and filtration were performed sequentially to obtain a urease solution. 12 parts by weight of 1 mol / L urea solution and 12 parts by weight of 1 mol / L calcium chloride solution were mixed, and then 5 parts by weight of urease solution were added. The mixture was stirred at 500 rpm for 2 min. Then, carbonic anhydrase-producing bacterial powder with a high alkali tolerance was added at a concentration of 8 g / L. The mixture was stirred again for 5 min to obtain a mineralized solution. S2.3: The surface-cleaned recycled aggregate from construction waste is pre-wetted with deionized water for 15 minutes, and then added to the mineralization solution to completely immerse the surface-cleaned recycled aggregate in the mineralization solution for 72 hours. After that, it is dried at 50°C until the moisture content reaches 10% to obtain mineralized recycled aggregate. S2.4: The mineralized recycled aggregate is fed into a high-speed vortex spray coating machine, and then a silicon-based composite functional liquid is sprayed through a dual-fluid atomizing spray gun. The spraying amount is controlled to be 3% of the aggregate mass. After the spraying is completed, the vortex state is maintained for 10 minutes. Then, hot air drying is carried out until the moisture content is ≤5% to obtain modified construction waste recycled aggregate. S3: Preparation of thermal insulation aerogel S3.1: Yttrium nitrate hexahydrate, tetraethyl orthosilicate, deionized water and phosphoric acid are mixed in a mass ratio of 0.3:1:1:0.01. After mixing, the mixture is stirred at 500 rpm for 10 h on a magnetic stirrer to obtain a mixed solution. 12 parts by weight of a 10 wt% polyvinyl alcohol aqueous solution are added to 12 parts by weight of the above mixed solution and stirred at 600 rpm for 4 h to obtain the precursor spinning solution. S3.2: The precursor spinning solution is injected into the needle tube for electrospinning. The needle tip is the positive electrode connected to a 17kV high-voltage power supply, and the aluminum foil receiving plate is the negative electrode grounded. The distance between the positive and negative electrodes is 22cm, and the feeding speed is 0.8mL / h to obtain the precursor fiber membrane. The precursor fiber membrane is dried in a forced-air drying oven at 60℃ for 40min. After drying, the precursor fiber membrane is transferred to a muffle furnace and heated to 250℃ at a rate of 2℃ / min, held for 2h, then heated to 800℃ at a rate of 5℃ / min, calcined for 3h, and finally cooled to room temperature at a rate of 4℃ / min to obtain the yttrium-doped silicon oxide nanofiber membrane. S3.3: Grind the above-mentioned yttrium-doped silica nanofiber membrane into short chopped fibers, mix 70 parts by weight of deionized water, 0.4 parts by weight of tetraethyl orthosilicate and 0.03 parts by weight of acetic acid, and stir at room temperature for 8 hours. Then add 0.2 parts by weight of the ground short chopped fibers and stir at 1500 r / min for 20 minutes to obtain the impregnation solution. S3.4: The unground yttrium-doped silica nanofiber membrane was completely immersed in the impregnation solution for 8 hours. After impregnation, the yttrium-doped silica nanofiber membrane was stacked layer by layer in a copper mold. Then, it was laterally frozen at -110°C for 12 minutes and then vacuum freeze-dried. After the vacuum freeze-dried aerogel preform was demolded, it was placed in an alumina crucible. The alumina crucible was then placed in an air resistance furnace and heated from room temperature to 230°C at a rate of 3°C / min. After holding at this temperature for 2 hours, the temperature was increased to 800°C at a rate of 3°C / min and held for another 2 hours. Finally, the temperature was lowered to room temperature at a rate of 2°C / min to obtain a thermal insulation aerogel. S4: Preparation of lightweight thermal insulation blocks S4.1: 70 parts by weight of modified construction waste recycled aggregate, 8 parts by weight of quartz sand, 15 parts by weight of hydrated sodium silicate and 30 parts by weight of fly ash are put into a high-speed mixer and stirred at 500 rpm for 8 min. Then, 12 parts by weight of composite cementitious agent, 3 parts by weight of hydroxypropyl starch and 15 parts by weight of deionized water are added and stirred at 300 rpm for 40 min to obtain block mixture. The composite cementitious agent is made by mixing gypsum powder and metakaolin in a weight ratio of 3:1. S4.2: Spread half of the block mixture into the bottom of the block mold and pre-press it flat. Then spread 1 part by weight of thermal insulation aerogel, then cover it with the remaining block mixture and scrape it flat. Press the block mixture into a block blank using a vibration pressing molding machine. Let the demolded block blank stand for 2 days, then transfer it to a constant temperature and humidity curing chamber. Set the curing temperature to 35℃ and the humidity to 75%RH and cure for 36 hours. Then place it in a natural environment for standard curing for 14 days. After curing, lightweight thermal insulation blocks are obtained.
[0026] Example 3, a method for preparing lightweight thermal insulation blocks based on construction waste, see [link to example]. Figure 1 ,include: S1: Preparation of Silicon-based Composite Functional Liquid S1.1: Take 17.5 parts by weight of N-aminoethyl-3-aminopropyltrimethoxysilane, 45 parts by weight of ethanol, 17.5 parts by weight of γ-glycidoxypropyltrimethoxysilane, and 55 parts by weight of deionized water, mix them, stir at 400 rpm, and let stand to defoam for 11 hours to obtain a mixed solution. S1.2: Add 1.75 parts by weight of sodium chloride to the mixed solution, then stir and mix at 550 rpm for 25 min. Then adjust the pH to neutral with 10 mol / L HCl solution, then add 7 parts by weight of boric acid, and then place it in a heat-collecting constant temperature magnetic stirrer and stir and react for 2.5 h at 56.5℃ and 400 rpm. Cool to room temperature to obtain silicon-based composite functional liquid. S2: Preparation of Modified Recycled Aggregate from Construction Waste S2.1: Remove impurities from construction waste, and crush the resulting waste concrete. Screen it through 5mm and 10mm square hole screens to obtain waste concrete with a continuous particle size of 5-10mm. Put the waste concrete into a rotary hot air vortex cleaner, set the temperature to 90℃ and the humidity to 20%RH, and process it for 32.5min. Then, screen out the stripped dust and broken mortar through a vibrating screen to obtain clean construction waste recycled aggregate. S2.2: 10 9 Cell / mL Bacillus pasteurellium lysate was lysed using an ultrasonic lysis method. After lysis, centrifugation and filtration were performed sequentially to obtain a urease solution. 11 parts by weight of 0.75 mol / L urea solution and 11 parts by weight of 0.75 mol / L calcium chloride solution were mixed, and then 4.5 parts by weight of urease solution were added. The mixture was stirred at 400 rpm for 1.5 min. After that, carbonic anhydrase-producing bacterial powder with a high alkali tolerance was added at a concentration of 6.5 g / L. The mixture was stirred again for 4 min to obtain a mineralized solution. S2.3: The surface-cleaned recycled aggregate from construction waste is pre-wetted with deionized water for 12.5 min, and then added to the mineralization solution to completely immerse the surface-cleaned recycled aggregate in the mineralization solution for 60 h. After that, it is dried at 47.5 ℃ to a moisture content of 9% to obtain mineralized recycled aggregate. S2.4: The mineralized recycled aggregate is fed into a high-speed vortex spray coating machine, and then a silicon-based composite functional liquid is sprayed through a dual-fluid atomizing spray gun. The spraying amount is controlled to be 2.5% of the aggregate mass. After the spraying is completed, the vortex state is maintained for 7.5 minutes. Then, hot air drying is carried out until the moisture content is ≤5% to obtain modified construction waste recycled aggregate. S3: Preparation of thermal insulation aerogel S3.1: Yttrium nitrate hexahydrate, tetraethyl orthosilicate, deionized water and phosphoric acid are mixed in a mass ratio of 0.3:1:1:0.01. After mixing, the mixture is stirred at 400 rpm for 9 h on a magnetic stirrer to obtain a mixed solution. 11 parts by weight of a 10 wt% polyvinyl alcohol aqueous solution are added to 11 parts by weight of the above mixed solution and stirred at 550 rpm for 3.5 h to obtain the precursor spinning solution. S3.2: The precursor spinning solution is injected into the needle tube for electrospinning. The needle tip is the positive electrode connected to a 17kV high-voltage power supply, and the aluminum foil receiving plate is the negative electrode grounded. The distance between the positive and negative electrodes is 22cm, and the feeding speed is 0.7mL / h to obtain the precursor fiber membrane. The precursor fiber membrane is dried in a forced-air drying oven at 55℃ for 35min. After drying, the precursor fiber membrane is transferred to a muffle furnace and heated to 250℃ at a rate of 2℃ / min, held for 1.5h, then heated to 750℃ at a rate of 4.5℃ / min, calcined for 2.5h, and finally cooled to room temperature at a rate of 4℃ / min to obtain the yttrium-doped silicon oxide nanofiber membrane. S3.3: Grind the above-mentioned yttrium-doped silica nanofiber membrane into short chopped fibers, mix 65 parts by weight of deionized water, 0.35 parts by weight of tetraethyl orthosilicate and 0.025 parts by weight of acetic acid, and stir at room temperature for 7 hours. Then add 0.19 parts by weight of the ground short chopped fibers and stir at 1400 r / min for 17.5 min to obtain the impregnation solution. S3.4: The unground yttrium-doped silica nanofiber membrane was completely immersed in the impregnation solution for 7 hours. After impregnation, the yttrium-doped silica nanofiber membrane was stacked layer by layer in a copper mold and then laterally frozen at -110°C for 11 minutes. After that, it was vacuum freeze-dried. The vacuum freeze-dried aerogel preform was demolded and placed in an alumina crucible. The alumina crucible was then placed in an air resistance furnace and heated from room temperature to 215°C at a rate of 2.5°C / min. After holding at this temperature for 1.5 hours, the temperature was increased to 750°C at a rate of 2.5°C / min and held for another 1.5 hours. Finally, the temperature was lowered to room temperature at a rate of 2°C / min to obtain a thermal insulation aerogel. S4: Preparation of lightweight thermal insulation blocks S4.1: 65 parts by weight of modified construction waste recycled aggregate, 6.5 parts by weight of quartz sand, 11.5 parts by weight of hydrated sodium silicate and 25 parts by weight of fly ash are put into a high-speed mixer and stirred at 450 rpm for 6.5 min. Then, 10 parts by weight of composite cementitious agent, 2.5 parts by weight of hydroxypropyl starch and 13.5 parts by weight of deionized water are added, and stirring is continued at 250 rpm for 35 min to obtain the block mixture. The composite cementitious agent is made by mixing gypsum powder and metakaolin in a weight ratio of 3:1. S4.2: Spread half of the block mixture into the bottom of the block mold and pre-press it flat. Then spread 0.75 parts by weight of thermal insulation aerogel, and then cover it with the remaining block mixture and scrape it flat. Press the block mixture into a block blank using a vibration pressing molding machine. Let the demolded block blank stand for 1.5 days, and then transfer it to a constant temperature and humidity curing chamber. Set the curing temperature to 32.5℃ and the humidity to 75%RH, and cure for 30 hours. Then place it in a natural environment for standard curing for 14 days. After curing, lightweight thermal insulation blocks are obtained.
[0027] Comparative Example 1 differs from Example 1 in that the carbonic anhydrase-producing bacterial powder in step S2.2 is replaced with an equal weight of urease solution, while the other steps remain unchanged in preparing lightweight thermal insulation blocks. This is referred to as Comparative Example 1.
[0028] Comparative Example 2 differs from Example 1 in that the urease solution in step S2.2 is replaced with an equal weight of carbonic anhydrase-producing bacterial powder resistant to high alkali, while the other steps remain unchanged in preparing lightweight thermal insulation blocks. This is referred to as Comparative Example 2.
[0029] Comparative Example 3 differs from Example 1 in that steps S1 and S2.4 are removed, while the remaining steps remain unchanged in preparing lightweight thermal insulation blocks. This is referred to as Comparative Example 3.
[0030] Comparative Example 4 differs from Example 1 in that the thermal insulation aerogel in steps S3 and S4.2 is removed, while the remaining steps remain unchanged to prepare a lightweight thermal insulation block, which is referred to as Comparative Example 4.
[0031] Comparative Example 5 differs from Example 1 in that it is a commercially available lightweight thermal insulation block, and is referred to as Comparative Example 5.
[0032] The compressive strength of the lightweight thermal insulation blocks of Examples 1-3 and Comparative Examples 1-3 and 5 was tested three times, and the average value was taken. The test results are shown in Table 1. The test standard was GB / T26538-2011.
[0033] Table 1. Results of compressive strength tests in Examples 1-3 and Comparative Examples 1-3 and 5
[0034] As can be seen from the data in Table 1, the mechanical strength of the present invention is better than that of commercially available lightweight thermal insulation blocks. Comparative Examples 1 and 2 show that urease and carbonic anhydrase bacteria powder have a synergistic effect during the mineralization process. The synergistic mineralization treatment of the two can significantly improve the compressive strength of the recycled aggregate. The compressive strength of Comparative Example 3 is reduced, indicating that the dense coating film and interfacial chemical bonding formed by the silicon-based composite functional liquid can effectively improve the compressive strength.
[0035] The thermal conductivity of the lightweight insulating blocks from Examples 1-3 and Comparative Examples 4 and 5 was measured three times, and the average value was taken. The results are shown in Table 2. The measurement standard was GB / T26538-2011.
[0036] Table 2. Results of thermal conductivity measurements for Examples 1-3 and Comparative Examples 4 and 5
[0037] As can be seen from the data in Table 2, the thermal insulation performance of the present invention is better than that of commercially available lightweight thermal insulation blocks. As can be seen from the data in Comparative Example 4, the thermal conductivity increases after removing the thermal insulation aerogel, resulting in a decrease in thermal insulation performance.
[0038] The freeze-thaw resistance and acid / alkali resistance of the lightweight thermal insulation blocks from Examples 1-3 and Comparative Example 3 were tested according to the freeze-thaw resistance test standard in GB / T4111-2013 "Test Methods for Concrete Blocks and Bricks". Acid and alkali corrosion environments were simulated using 5% sulfuric acid solution and 5% sodium hydroxide solution. Acid and alkali resistance were tested according to GB / T50082-2009 "Standard for Test Methods for Long-Term Performance and Durability of Ordinary Concrete". Three tests were performed, and the average value was taken. The results are shown in Table 3.
[0039] Freeze-thaw resistance: The blocks were placed in a fully automatic low-temperature freeze-thaw tester. The freezing temperature was controlled at -15℃ and the freezing time was 4 hours. The thawing water temperature was controlled at 20℃ and the thawing time was 4 hours. This constitutes one freeze-thaw cycle. After 50 freeze-thaw cycles, the compressive strength loss rate was calculated, and the appearance after 50 freeze-thaw cycles was observed.
[0040] Table 3. Results of freeze-thaw resistance and acid / alkali resistance tests of Examples 1-3 and Comparative Example 3
[0041] As can be seen from the data in Table 3, Comparative Example 3, which removed the silicon-based composite functional liquid coating process, suffered severe freeze-thaw damage. This demonstrates that the dense coating film formed by the silicon-based composite functional liquid effectively blocked the pores on the surface of the aggregate, preventing water molecules from penetrating into the internal channels and freezing and expanding, thus significantly improving the freeze-thaw resistance of the blocks. The mass loss rate of Examples 1-3 under strong acid and strong alkali erosion was significantly lower than that of Comparative Example 3. Comparative Example 3, which was not coated with silicon-based composite functional liquid, had a weak transition zone at the aggregate-cement matrix interface. Acid radicals and alkali metal ions easily penetrated and reacted along the interface, leading to the decomposition of cement hydration products and poor acid and alkali resistance.
[0042] It should be understood that those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims. Parts not described in detail in this specification are prior art known to those skilled in the art.
Claims
1. A lightweight thermal insulation block based on construction waste, characterized in that, include: 60-70 parts by weight of modified recycled construction waste aggregate, 5-8 parts by weight of quartz sand, 8-15 parts by weight of hydrated sodium silicate, 20-30 parts by weight of fly ash, 8-12 parts by weight of composite cementitious agent, 2-3 parts by weight of modified starch, 12-15 parts by weight of deionized water and 0.5-1 parts by weight of thermal insulation aerogel. Modified construction waste recycled aggregate is obtained by first removing impurities from construction waste, crushing and screening, washing, then performing compound mineralization treatment with urease and high-alkali resistant carbonic anhydrase bacteria, spraying and coating with silicon-based composite functional liquid, and drying.
2. A method for preparing lightweight thermal insulation blocks based on construction waste, used to prepare the lightweight thermal insulation blocks based on construction waste as described in claim 1, characterized in that, include: S1: Preparation of silicon-based composite functional liquid; Mix 15-20 parts by weight of N-aminoethyl-3-aminopropyltrimethoxysilane, 40-50 parts by weight of ethanol, 15-20 parts by weight of γ-glycidyl etheroxypropyltrimethoxysilane, and 50-60 parts by weight of deionized water, stir, let stand to defoam, add sodium chloride and stir, adjust the pH to neutral, add boric acid, stir the reaction at a constant temperature, and cool to obtain a silicon-based composite functional liquid. S2: Preparation of modified recycled aggregate from construction waste; After construction waste is cleaned, crushed, screened, and washed, it undergoes mineralization treatment, and is finally sprayed with a silicon-based composite functional liquid and dried to obtain modified construction waste recycled aggregate. S3: Preparation of thermal insulation aerogel; Yttrium nitrate hexahydrate, tetraethyl orthosilicate, deionized water, and phosphoric acid were mixed in a specific ratio and magnetically stirred for a long time. Then, a polyvinyl alcohol solution was added and stirred to prepare a spinning precursor solution. The fiber membrane was obtained by electrospinning under high pressure, electrode spacing, and push speed. The fiber membrane was dried and calcined in stages to obtain yttrium-doped silica nanofibers. The fibers were ground and chopped, and then mixed with tetraethyl orthosilicate and acetic acid aqueous solution to prepare an impregnation solution. The fiber membrane was impregnated, stacked, frozen, and vacuum dried. Finally, it was calcined in stages at high temperature to obtain a thermal insulation aerogel. S4: Preparation of lightweight thermal insulation blocks; Modified recycled aggregate from construction waste, quartz sand, hydrated sodium silicate, and fly ash are mixed together, and then composite binder, modified starch, and deionized water are added and stirred to obtain a mixture. Then, thermal insulation aerogel is laid in the block mixture, and after vibration and pressure molding, static setting, and curing, lightweight thermal insulation blocks are obtained.
3. The method for preparing lightweight thermal insulation blocks based on construction waste according to claim 2, characterized in that, S1: The preparation of the silicon-based composite functional liquid includes the following steps: S1.1: Take 15-20 parts by weight of N-aminoethyl-3-aminopropyltrimethoxysilane, 40-50 parts by weight of ethanol, 15-20 parts by weight of γ-glycidoxypropyltrimethoxysilane, and 50-60 parts by weight of deionized water, mix them, stir at 300-500 rpm, and let stand to defoam for 10-12 hours to obtain a mixed solution; S1.2: Add 1.5-2 parts by weight of sodium chloride to the mixed solution, then stir and mix at 500-600 rpm for 20-30 min. Adjust the pH to neutral with 10 mol / L HCl solution, then add 6-8 parts by weight of boric acid. Place the mixture in a heat-collecting constant temperature magnetic stirrer and react at 55-58℃ and a stirring speed of 300-500 rpm for 2-3 h. Cool to room temperature to obtain the silicon-based composite functional liquid.
4. The method for preparing lightweight thermal insulation blocks based on construction waste according to claim 3, characterized in that, S2: Preparation of modified recycled aggregate from construction waste, specifically including the following steps: S2.1: Remove impurities from construction waste, and crush the resulting waste concrete. Then, screen it through 5mm and 10mm square hole screens to obtain waste concrete with a continuous particle size of 5-10mm. Put the waste concrete into a rotary hot air vortex cleaner and process it for 25-40 minutes. After that, screen out the stripped dust and broken mortar through a vibrating screen to obtain clean construction waste recycled aggregate. S2.2: 10 9 Cell / mL Bacillus pasteurellium lysate was lysed using an ultrasonic lysis method. After lysis, centrifugation and filtration were performed sequentially to obtain a urease solution. 10-12 parts by weight of 0.5-1 mol / L urea solution and 10-12 parts by weight of 0.5-1 mol / L calcium chloride solution were mixed, and then 4-5 parts by weight of urease solution were added. The mixture was stirred at 300-500 rpm for 1-2 min. After that, carbonic anhydrase-producing bacterial powder tolerant to high alkali was added, and the mixture was stirred again for 3-5 min to obtain a mineralized solution. S2.3: The surface-cleaned recycled aggregate from construction waste is pre-wetted with deionized water for 10-15 minutes, and then added to the mineralization solution to completely immerse the surface-cleaned recycled aggregate in the mineralization solution for 48-72 hours. After that, it is dried in an environment of 45-50℃ until the moisture content reaches 8-10% to obtain mineralized recycled aggregate. S2.4: The mineralized recycled aggregate is fed into a high-speed vortex spray coating machine, and a silicon-based composite functional liquid is sprayed through the spraying device. The spraying amount is controlled to be 2-3% of the aggregate mass. After the spraying is completed, the vortex state is maintained for 5-10 minutes. Then, hot air drying is carried out until the moisture content is ≤5% to obtain modified construction waste recycled aggregate.
5. The method for preparing lightweight thermal insulation blocks based on construction waste according to claim 4, characterized in that, In step S2.1, the temperature of the rotary hot air vortex cleaner is 80-100℃ and the humidity is 10-30%RH.
6. The method for preparing lightweight thermal insulation blocks based on construction waste according to claim 4, characterized in that, In step S2.3, the amount of carbonic anhydrase-producing bacterial powder added is 5-8 g / L based on the total volume of the mineralization solution, and the viable count of the carbonic anhydrase-producing bacterial powder is 1×10⁻⁶. 9 CFU / g.
7. The method for preparing lightweight thermal insulation blocks based on construction waste according to claim 2, characterized in that, S3: Preparation of thermal insulation aerogel, specifically including the following steps: S3.1: Mix yttrium nitrate hexahydrate, tetraethyl orthosilicate, deionized water and phosphoric acid in a mass ratio of 0.3:1:1:0.
01. After mixing, stir the mixture in a magnetic stirrer at 300-500 rpm for 8-10 h to obtain a mixed solution. Add 10-12 parts by weight of a 10 wt% polyvinyl alcohol aqueous solution to 10-12 parts by weight of the above mixed solution and stir at 500-600 rpm for 3-4 h to obtain the precursor spinning solution. S3.2: Inject the precursor spinning solution into the syringe for electrospinning. The needle tip is the positive electrode connected to a 17kV high-voltage power supply, and the aluminum foil receiving plate is the negative electrode grounded. The distance between the positive and negative electrodes is 20-22cm, and the feeding speed is 0.6-0.8mL / h to obtain the precursor fiber membrane. Dry the precursor fiber membrane in a forced-air drying oven at 50-60℃ for 30-40min. After drying, transfer the precursor fiber membrane to a muffle furnace and heat it to 250℃ at a rate of 2℃ / min. Hold it at this temperature for 1-2h, then heat it to 700-800℃ at a rate of 4-5℃ / min and calcine it for 2-3h. Finally, cool it to room temperature at a rate of 4℃ / min to obtain the yttrium-doped silicon oxide nanofiber membrane. S3.3: Grind the above-mentioned yttrium-doped silica nanofiber membrane into short chopped fibers. Mix 60-70 parts by weight of deionized water, 0.3-0.4 parts by weight of tetraethyl orthosilicate and 0.02-0.03 parts by weight of acetic acid, and stir at room temperature for 6-8 hours. Then add 0.18-0.2 parts by weight of the ground short chopped fibers and stir at 1300-1500 r / min for 15-20 minutes to obtain the impregnation solution. S3.4: The unground yttrium-doped silica nanofiber membrane was completely immersed in the impregnation solution for 6-8 hours. After impregnation, the yttrium-doped silica nanofiber membrane was stacked layer by layer in a copper mold and laterally frozen at -110°C for 10-12 minutes. Then, it was vacuum freeze-dried. After the vacuum freeze-dried aerogel preform was demolded, it was placed in an alumina crucible. The alumina crucible was then placed in an air resistance furnace and heated from room temperature to 200-230°C at a rate of 2-3°C / min. After holding at this temperature for 1-2 hours, the temperature was increased to 700-800°C at a rate of 2-3°C / min and held for another 1-2 hours. Finally, the temperature was lowered to room temperature at a rate of 2°C / min to obtain a thermal insulation aerogel.
8. The method for preparing lightweight thermal insulation blocks based on construction waste according to claim 2, characterized in that, S4: The preparation of lightweight thermal insulation blocks includes the following steps: S4.1: Put 60-70 parts by weight of modified construction waste recycled aggregate, 5-8 parts by weight of quartz sand, 8-15 parts by weight of hydrated sodium silicate and 20-30 parts by weight of fly ash into a high-speed mixer and stir at 400-500 rpm for 5-8 minutes. Then add 8-12 parts by weight of composite cementitious agent, 2-3 parts by weight of modified starch and 12-15 parts by weight of deionized water, and continue to stir at 200-300 rpm for 30-40 minutes to obtain the block mixture. S4.2: Spread half of the above-mentioned block mixture into the bottom of the block mold and pre-press it flat. Then spread 0.5-1 parts by weight of thermal insulation aerogel, cover it with the remaining block mixture and scrape it flat. Press the block mixture into block blanks using a vibration pressing molding machine. Let the demolded block blanks stand for 1-2 days, then transfer them to a constant temperature and humidity curing chamber. Set the curing temperature to 30-35℃ and the humidity to 75%RH, and cure for 24-36 hours. Then place them in a natural environment for standard curing for 14 days. After curing, lightweight thermal insulation blocks are obtained.
9. A method for preparing lightweight thermal insulation blocks based on construction waste according to claim 8, characterized in that, The composite gelling agent in step S4.1 is made by mixing gypsum powder and metakaolin in a weight ratio of 3:
1.
10. A method for preparing lightweight thermal insulation blocks based on construction waste according to claim 8, characterized in that, The modified starch in step S4.1 is hydroxypropyl starch.